Investigation of the Psychological Capital of Security Employees by Nationality and Status - Avcı, Abdülkadir; Erdem, Ramazan (European Journal of Multidisciplinary Studies, 2022)
The concept of psychological capital (PsyCap) recently has attracted a great deal of interest who has been studying on organizational behavior. Psychological capital can be defined as individual’s positive psychological state which contributes both personal and organizational aims and improves human performance. It is accepted that psychological capital has four components: self-efficacy, optimism, hope and resiliency. The purpose of the present study is to examine the associations of psychological capital (PsyCap) of security employees by nationality and status. In this study a cross-sectional survey was conducted using a convenience sample of 336 security employees in a military organization to establish possible relationship between psychological capital and two of demographic variables (nationality and status). The data obtained by the survey was analyzed using the SPSS 21.0 package program. In statistical analyzes, T-test and variance (ANOVA) analyzes were used. The results of the data has showed that resiliency of civil employees differs significantly from officers and noncommissioned officers. The analysis has also showed that self-efficacy and hope of Turkey participants differ significantly from European countries participants. However, no statistically significant difference has been found in resiliency of participant countiries.
Keywords: Psychological capital, nationality, status, security employees.